Volvariella volvacea (paddy straw mushroom): A mushroom with exceptional medicinal and nutritional properties - Sadaqat Ali; Nousheen Yousaf; Muhammad Usman; Muhammad Ammar Javed; Maryam Nawaz; Baber Ali; Muhammad Azam; Sezai Ercisli; Serpil Tirasci; Ahmed Ezzat Ahmed (Heliyon)
Volvariella volvacea, commonly referred to as paddy straw mushroom, is renowned for its remarkable medicinal and nutritional properties. This mushroom, part of the family Pluteaceae, thrives in tropical and subtropical regions and is highly esteemed for its distinctive flavor and substantial health benefits. The fruiting body of V. volvacea is a rich source of bioactive compounds, including antioxidant enzymes, terpenes, polypeptides, sugars, phenolics, and flavonoids. These compounds exhibit an extensive range of therapeutic activities such as anti-tumor, anti-microbial, antioxidant, anti-malarial, anti-cancer, anti-inflammatory, and anti-allergic effects. Nutritionally, V. volvacea is an excellent source of carbohydrates, proteins, fibers, ascorbic acid, and essential minerals. It also boasts a comprehensive profile of amino acids, including valine, arginine, glutamine, serine, aspartic acid, leucine, isoleucine, tyrosine, asparagine, lysine, cystine, proline, glycine, tryptophan, methionine, phenylalanine, threonine, and histidine. This review emphasizes the significant medicinal and nutritional potential of V. volvacea, advocating its inclusion as a functional food to enhance human health and well-being. By highlighting its diverse bioactive compounds and therapeutic benefits, this review aims to foster greater recognition and utilization of paddy straw mushroom in both dietary and medicinal applications.